Classroom based cognitive behavioural therapy in reducing symptoms of depression in high risk adolescents: pragmatic cluster randomised controlled trial. (5th October 2012) - Stallard, Paul; Sayal, Kapil; Phillips, Rhiannon; Taylor, John A; Spears, Melissa; Anderson, Rob; Araya, Ricardo; Lewis, Glyn; Millings, Abigail; Montgomery, Alan A
Abstract : Objective To compare the effectiveness of classroom based cognitive behavioural therapy with attention control and usual school provision for adolescents at high risk of depression. Design Three arm parallel cluster randomised controlled trial. Setting Eight UK secondary schools. Participants Adolescents (n=5030) aged 12-16 years in school year groups 8-11. Year groups were randomly assigned on a 1:1:1 ratio to cognitive behavioural therapy, attention control, or usual school provision. Allocation was balanced by school, year, number of students and classes, frequency of lessons, and timetabling. Participants were not blinded to treatment allocation. Interventions Cognitive behavioural therapy, attention control, and usual school provision provided in classes to all eligible participants. Main outcome measures Outcomes were collected by self completed questionnaire administered by researchers. The primary outcome was symptoms of depression assessed at 12 months by the short mood and feelings questionnaire among those identified at baseline as being at high risk of depression. Secondary outcomes included negative thinking, self worth, and anxiety. Analyses were undertaken on an intention to treat basis and accounted for the clustered nature of the design. Results 1064 (21.2%) adolescents were identified at high risk of depression: 392 in the classroom based cognitive behavioural therapy arm, 374 in the attention control arm, and 298 in the usual school provision arm. At 12 months adjusted mean scores on the short mood and feelings questionnaire did not differ for cognitive behavioural therapy versus attention control (−0.63, 95% confidence interval −1.85 to 0.58, P=0.41) or for cognitive behavioural therapy versus usual school provision (0.97, −0.20 to 2.15, P=0.12). Conclusion In adolescents with depressive symptoms, outcomes were similar for attention control, usual school provision, and cognitive behavioural therapy. Classroom based cognitive behavioural therapy programmes may result in increased self awareness and reporting of depressive symptoms but should not be undertaken without further evaluation and research. Trial registration Current Controlled Trials ISRCTN19083628 .